The Florida SLE Mosquito, Culex (Culex) nigripalpus Theobald (Insecta: Diptera: Culicidae) - J.F. Day (EDIS)
This document is part of The Featured Creatures collection. The Florida SLE mosquito, Culex nigripalpus, is a significant disease vector in Florida, primarily transmitting St. Louis encephalitis (SLE) and potentially eastern equine encephalitis (EEE) viruses. This mosquito species thrives in subtropical regions and prefers laying eggs in freshly flooded habitats. Due to its abundance and behavior, it poses a considerable risk for arboviral transmission, necessitating vigilant surveillance and management efforts.